Effects of Carbetocin and Oxytocin on Haemodynamic among Women with Post-Partum Hemorrhage after Caesarean Section: A Single Blind Parallel Arm Randomized Controlled Trial (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Management of haemodynamic among women with post-partum hemorrhage after caesarean section.Objective: The purpose of the present study was to compare the effect of carbetocin and oxytocin on haemodynamic among women with post-partum hemorrhage after caesarean section.Methodology: This randomized controlled trial was conducted in the Department of Obstetrics and Gynaecology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2015 to December 2015 for a period of six months. Pregnant women diagnosed on the standard criteria admitted in BSMMU, Dhaka, Bangladesh were selected as study population by consecutive type of sampling. Randomization was performed according to computer generated simple random sampling method. An Uterotonic was an agent used to induce contraction or greater tonicity of the uterus. Then the patients were monitored per operatively and post operatively. All the information was recorded in data collection sheet. Main outcome variables were estimated blood loss.Results: A total number of 96 pregnant women were recruited for this s tudy of which 48 cases were enrolled in group I and the rest of 48 case were enrolled in group II. The mean age with SD of the group I and group II were 24.4±4.7 years and 24.7±3.7 years (p=0.729). Before administration of drug, mean systolic blood pressure was found 115.6±5.8 mmHg in group I and 114.8±7.8 mmHg in group II. At 24 hours after caesarean section, mean systolic blood pressure was found 116.9±5.8 mmHg in group I and 113.9±8.8 mmHg in group II (p>0.05). Before administration of drug, mean diastolic blood pressure was found 75.8±7.9 mmHg in group I and 76.9±9.9 mmHg in group II. At 24 hours after caesarean section, mean diastolic blood pressure was found 76.7±6.6 mmHg in group I and 76.1±7.2 mmHg in group II (p>0.05). Before administration of drug, mean maternal blood loss was found 376.4±110.4 ml in group I and 439.4±199.9 ml in group II. At 24 hours after caesarean section, mean maternal blood loss was found 468.2±121.9 ml in group I and 532.6±243.0 ml in group II (p>0.05).Conclusion: In conclusion the systolic blood pressure, diastolic blood pressure and blood loss are not significantly varied in group I and II.Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):141-146